Impact of TV Commercial, Social Media Advertising, and Point of Purchase on Brand Awareness Leading to Consumer Buying Intention on Brand “Cap Panda” - Henry Sugiarto Prasetyo; Hendra Achmadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study analyzes the relationship between TV commercial advertisements, social media, and the formation of a relationship with the point of purchase on Brand Awareness that influences the decision to buy the FMCG product "Cap Panda". This ready to drink brand is well known of its product variants "liang tea" and grass jelly. This research using descriptive analysis according to the respective variables in the research model and their reflective indicators will be explained below. The value obtained comes from the overall answers of 160 research respondents from urban area such as Jakarta and Surabaya, according to the data input in the PLS-SEM. The results showed that of the three independent variables, TV and Social Media advertisements had a positive effect on the formation of Brand Awareness. Meanwhile, Point of Purchase showed negative significance. However, despite the establishment of Brand Awareness of the product “Cap Panda”, at least it is able to generate consumer buying intentions, especially related to liang tea products which are very recognizable.